The changing purpose of mental health law: From medicalism to legalism to new legalism. (July 2016) - Brown, Jennifer
Abstract: The role of law in regulating mental health detention has come to engender great contention in the legal and sociological disciplines alike. This conflict is multifaceted but is centred upon the extent to which law should control the psychiatric power of detention. In this manner the evolution of law regulating mental health detention has been seen in terms of a pendulous movement between two extremes of medicalism and legalism. Drawing on socio-legal literature, legislation, international treaties and case law this article examines the changing purpose of mental health law from an English and Council of Europe perspective by utilizing the concepts of medicalism, legalism and new legalism as descriptive devices before arguing that the UN Convention on the Rights of Persons with Disabilities goes further than all of these concepts and has the potential to influence mental health laws internationally.